2021
DOI: 10.36227/techrxiv.16698469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fundamental Limitations and State-of-the-art Solutions for Target Node Localization in WSNs

Abstract: <p> </p><p>With the advances in new technological trends and the reduction in prices of sensor nodes, wireless sensor networks</p> <p>(WSNs) and their applications are proliferating in several areas of our society such as healthcare, industry, farming, and housing. Accordingly, in recent years attention on localization has increased significantly since it is one of the main facets in any WSN. In a nutshell, localization is the process in which the position of any sensor node is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 199 publications
(233 reference statements)
0
3
0
Order By: Relevance
“…It has been shown that the localization accuracy increases with the number of anchors [74,75]. Nevertheless, in some scenarios the number of available anchors is low for different reasons such as battery exhaustion or limited communication range [76]. Hence, the localization is limited in these cases.…”
Section: Fundamental Limitations Impacting Localization 111 Number Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the localization accuracy increases with the number of anchors [74,75]. Nevertheless, in some scenarios the number of available anchors is low for different reasons such as battery exhaustion or limited communication range [76]. Hence, the localization is limited in these cases.…”
Section: Fundamental Limitations Impacting Localization 111 Number Of...mentioning
confidence: 99%
“…The distribution and deployment of anchor nodes play an important role in the localization algorithm. If the anchors are placed only in some portion of the area of interest, it does not guarantee that all unknown nodes reside inside the convex hull formed by the anchors resulting in a low localization accuracy [76]. The geometric dilution of precision (GDOP) is a parameter used to interpret the relation between anchor distribution and accuracy which increases as the value of GDOP decreases [77].…”
Section: Distribution Of Anchorsmentioning
confidence: 99%
See 1 more Smart Citation